Non‐Covalent Polymer Surface Modification of Cellulose Nanocrystals Using Block Copolymers. Issue 3 (23rd December 2021) - Torres‐Rocha, Olga Lidia; Campbell, Sophie; Woodcock, Nicole; Pinaud, Julien; Lacroix‐Desmazes, Patrick; Champagne, Pascale; Cunningham, Michael F.
Abstract: Cellulose nanocrystals (CNC) possess desirable mechanical and optical properties that make them a candidate in the development of the next generation of polymer‐based composites. However, CNC also have a critical issue associated with their use: their hydrophilicity and incompatibility with hydrophobic polymers. CNC surface properties must be modified for them to be successfully implemented by the industrial sector. Grafting (co)polymers chains on the CNC surface can provide compatibility to CNC with hydrophobic matrices and expand their potential range of applications. In this communication preliminary results of a simple method to functionalize CNC surface are reported using block copolymers, where a cationic block anchors via complexation to the anionically charged CNC surface and the other block acts as a stabilizing block, providing dispersibility in various solvents. This is a much simpler and less expensive method than current routes based on covalent modification. The block copolymers poly(polyethylene glycol methacrylate) ‐b‐ poly(N‐butyl‐N′‐vinyl imidazolium bromide) (PPEGMA ‐b‐ PBuVIm) and poly(styrene) ‐b‐ PBuVIm (PS ‐b‐ PBuVIm) are first synthesized via nitroxide‐mediated polymerization and then non‐covalently adsorbed on the CNC surface. The functionalization has been confirmed via FT‐IR and TGA. The dispersion of polymer‐modified CNC materials in organic solvents is evaluated via dynamic light scattering. Modified CNC yielded stable dispersions in organic solvents. Abstract : A simpler and efficient method to functionalize the CNC surface using block copolymers is presented, where a cationic block anchors via complexation to the anionically charged CNC surface and the other block acts as a stabilizing block which provides dispersibility in various organic solvents.